2022
DOI: 10.3390/su14095690
|View full text |Cite
|
Sign up to set email alerts
|

How Stable Are Students’ Entrepreneurial Intentions in the COVID-19 Pandemic Context?

Abstract: The purposed longitudinal study analyzes the evolution of students’ Entrepreneurial Intentions (EI) and its antecedents over the COVID-19 pandemic period and explores the inter-individual differences and the intra-individual changes. Our main contribution consists of proposing two-panel estimations techniques: first, a Latent Change Score model (LCS) approach to analyze the stability of our constructs, and second, a Generalized Least Squares (GLS) Random-Effect estimation of a complex network of relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Ruiz-Rosa et al [6] found that Spanish university students' social entrepreneurial intention decreased during COVID-19 [9], and similar results were found among Latin American students [10]. However, Botezat and colleagues found that Romanian college students' EI increased during the pandemic, but this study did not distinguish the impact of the entrepreneurship education program from the impact of the pandemic [11]. Future research should compare different countries' results because different countries have different cultural backgrounds [53] and different entrepreneurial environments [69].…”
Section: Research Values and Contributionsmentioning
confidence: 63%
See 1 more Smart Citation
“…Ruiz-Rosa et al [6] found that Spanish university students' social entrepreneurial intention decreased during COVID-19 [9], and similar results were found among Latin American students [10]. However, Botezat and colleagues found that Romanian college students' EI increased during the pandemic, but this study did not distinguish the impact of the entrepreneurship education program from the impact of the pandemic [11]. Future research should compare different countries' results because different countries have different cultural backgrounds [53] and different entrepreneurial environments [69].…”
Section: Research Values and Contributionsmentioning
confidence: 63%
“…In the context of the pandemic, a number of studies have found that college students' EI has decreased [9,10]. However, there are also studies that have found that college students' EI has increased [11]. Despite the conflicting results, these studies do not delve into what causes this.…”
Section: Introductionmentioning
confidence: 97%
“…Second, others provide compelling evidence that gender diversity impacts commercial and social EI (Lortie et al, 2017;Molino et al, 2018). Preliminary evidence revealed that women regarded the COVID-19 pandemic as a chance to display greater EI than males (Botezat et al, 2022;Ettis, 2022;Ragazou et al, 2022). However, another researcher supplied compelling evidence demonstrating the display of higher EI by men than women (Birhanu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Risk control is a robust component of entrepreneurship education and must be considered in the curriculum. During the COVID-19 pandemic, students’ EI has improved through their enrollment in their universities’ entrepreneurship education programs (Botezat et al , 2022). In Chinese colleges, there is a greater insistence on entrepreneurship education.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 99%
“…These are found mainly in the developing economies (Chowdhury, 2007; Anwar et al , 2021; Linfang et al , 2021; Othman et al (2022). It is suggested, also, that ATR, FOF, legal issues and motivational barriers have a more harmful influence on entrepreneurship (Nawaser et al , 2011; Botezat et al , 2022).…”
Section: Introductionmentioning
confidence: 99%